ANALYSIS OF MATHEMATICS PROBLEM SOLVING ABILITY IN ELEMENTARY SCHOOL HOTS PROBLEM SOLVING - Siti Nur Isnaini; Nadra Hafizah; Yanti Fitria (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2023)
The purpose of this study is to describe students' mathematical problem-solving abilities when answering HOTS questions on the material scale. The research method is descriptive, qualitative, and quantitative. The subjects of this study were students, namely 32 students of SD Negeri 36 Payakumbuh who had been taught scale material. The data collected are the written responses of the students as well as the results of student interviews. Problem-solving ability is measured by referring to the indicators of the National Council of Teachers of Mathematics (NCTM). From the results of the written answer data analysis, the researcher determined 6 research subjects, namely, 2 subjects each belonging to the upper, middle, and lower groups. The results of this study indicate the ability of group problem solving to be able to understand the problem and choose the right, systematic strategy. Middle-class problem-solving ability is defined as the ability to understand the problem, select the best strategy, and not be methodical. Lower-class problem-solving ability: unable to understand the problem, unable to choose the right strategy, and not systematic in solving the problem.